Fauna Krustasea di Perairan Kepulauan Anambas, Propinsi Kepulauan Riau - Ernawati Widyastuti (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2007)
Observation of crustacean fauna in Anambas Islands waters was conducted from 20 May to 4 June 2002. The selected locations were Ranap Island, Matak Island, Pemutus Island, Akar Island, and Jemaja Island. The aim of this study was to know the diversity and evenness of the crustacean species. Sampling was conducted by applying quadrant transect and other collections. Forty one species of crustaceans, representing 14 families, were collected from those selected locations including 23 species that were collected from transect area. The results showed that diversity index of the crustacean fauna was 0.65 to 0.98 and species evenness was 0.85 to 0.98. Based on the species diversity index, all those selected locations could be said as having low diversity.